PENGEMBANGAN SISTEM INFORMASI MANAJEMEN ALUMNI BERBASIS WEB DI MA UMMUL AKHYAR - Amanda Januareta, Dhea; Dwi Pamungkas, Bian; Rozi, Fahrur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Alumni information management plays an important role in supporting educational institutions in maintaining alumni records and providing accurate information for administrative and institutional development purposes. However, the alumni data management process at MA Ummul Akhyar was still carried out using spreadsheet software, making the data vulnerable to loss due to the absence of a centralized and secure storage system. This study aimed to develop a web-based Alumni Management Information System to improve the effectiveness, efficiency, and security of alumni data management. The study employed a Research and Development (R&D) approach using the eXtreme Programming (XP) software development model, which consisted of the planning, design, coding, testing, and software increment stages. The developed system was evaluated using the ISO/IEC 25010 software quality standard on the Functional Suitability and Compatibility aspects, while usability was assessed using the System Usability Scale (SUS). The evaluation results showed that both the Functional Suitability and Compatibility aspects achieved a score of 100%. In addition, the usability testing produced an average SUS score of 94.5 in the small-group trial and 95.87 in the large-group trial, both categorized as Grade A with an Excellent rating. These findings indicate that the developed system is highly feasible, easy to use, and capable of supporting alumni data management at MA Ummul Akhyar in a more effective, secure, and integrated manner.